Chiral Metal–Organic Framework Hollow Nanospheres for High-Efficiency Enantiomer Separation - Wang, X.; Zhu, Y.; Liu, Jian; Liu, C.; Cao, C.; Song, W. (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Chiral ZIF-8 hollow nanospheres with d-histidine as part of chiral ligands (denoted as H-d-his-ZIF-8) were prepared for separation of (±)-amine acids. Compared to bulk d-his-ZIF-8 without a hollow cavity, the prepared H-d-his-ZIF-8 showed 15 times higher separation capacity and higher ee values of 90.5 % for alanine, 95.2 % for glutamic acid and 92.6 % for lysine, respectively.